A multi-site prospective, observational study of physiotherapist independent prescribing activity across musculoskeletal clinics in the United Kingdom. (October 2022) - Noblet, Tim; Jadhakhan, Feroz; Bennett, Andrew; McCrum, Carol; O'Shea, Simon; Hensman- Crook, Amanda; Barratt, Paul; Regan, Paul; Ronan, Lynne; Baker, Dave; Rushton, Alison
Abstract: Objective: To establish how advanced practice physiotherapists in the UK working in the musculoskeletal specialty are utilising their independent non-medical prescribing skills. Design: Multi-site, prospective, descriptive observational study. Ethics reference No: ERN_19–0994). Method: The study was conducted by seven advanced practitioners, across seven clinical sites representative of advanced musculoskeletal practice in the UK, between 1st October 2019–March 31, 2020. Advanced physiotherapy practitioner independent prescribers working in a variety of musculoskeletal specialty areas collected data across 5 contexts of musculoskeletal clinical service: first contact practice, primary care, community triage, secondary care orthopaedics, secondary care rheumatology and private practice. Quantitative data were analysed descriptively with qualitative data analysed/synthesised via thematic analysis. Results: Prescribing activity data for n = 2470 patients were collected. Prescribing activity was highest for the treatment of nociceptive pain (51.3%) and inflammation (39.6%). Most prescribing activity occurred in the first 2–6 weeks (34.1%) following onset of condition. Medicines optimisation accounted for most of prescribing activity (18.1%), followed by over-the-counter medication recommendation (15.5%). De-prescribing accounted for 10.8% of all prescribing activity recorded. Qualitative data were synthesised into 4 themes: multimodal physiotherapeutic approach, joint decision making and patient choice, working with complexity, and legal and regulatory restriction. Conclusions: Physiotherapist independent prescribing was used within all health sectors in conjunction with advanced skills in musculoskeletal physiotherapy as part of a multimodal physiotherapeutic approach. Prescribing activity was dictated by the clinicians' clinical reasoning and use of joint decision-making. Prescribing activity for acute back and neuropathic radicular pain was limited secondary to recent reclassification of gabapentin and pregabalin. Highlights: This is the first study to describe how physiotherapists utilise non-medical prescribing. Physiotherapy prescribing was used within a multimodal physiotherapeutic approach. Findings should inform future implementation & utilisation of physiotherapist prescribing.